KEMAMPUAN MENULIS TEKS PERSUASIF MELALUI MEDIA GAMBAR OLEH SISWA KELAS VIII SMP NEGERI 20 KUPANG - LIPISIALA, APRILIA; DJULI, LABU; Makan Malay, Narantoputrayadi (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
The focus of this study is “How well can eighth-grade students at SMP Negeri 20 Kupang write persuasive texts?” The purpose of this study is to determine the ability of eighth-grade students at SMP 20 Kupang to write persuasive texts using images. The benefits of this study are theoretical and practical. The method used in this research is a qualitative descriptive method with 23 eighth-grade students at SMP Negeri 20 Kupang as the subjects. The research instrument used is the students' work. Data collection was carried out using a test technique. The data analysis technique was to test the collected data. The results showed that out of 23 students, only 12 students were able to write persuasive texts, while the structure of the students' text in terms of issue recognition reached 26.9%, 35.2% in the argument sequence aspect, 29.1% in the appeal statement aspect, and 30.4% in the reaffirmation aspect. Based on the data analysis results, it can be concluded that the ability of eighth-grade students at SMP Negeri 20 Kupang in writing persuasive texts using image media is in the less capable category.